The Effect of Corporate Social Responsibility (CSR), Relationship Marketing and Shariah Compliance on Customer Loyalty with Customer Emotional Response As Intervening - Hesti Dwi Lestari; Imanda Firmantyas Putri Pertiwi (Social Science Studies, 2022)
This study aims to determine how strong the influence of Corporate Social Responsibility (CSR), Relationship Marketing and Shariah Compliance on Customer Loyalty with Customer Emotional Response as an intervening variable. This research uses quantitative methods by processing primary data obtained through distributing questionnaires to people who are customers of Bank Muamalat Indonesia. The sample taken was 50 respondents using purposive sampling technique, then the results obtained were processed with SPSS version 22. The analysis used included descriptive statistical tests, instrument tests, classical assumption tests, model accuracy tests, hypothesis tests and path analysis. Based on the results of the test, the results obtained: CSR has a significant positive effect on customer emotional response. Marketing relations have a significant positive effect on customer emotional responses. Shariah compliance has no significant negative effect on customer emotional response. CSR has a significant positive effect on loyalty. Relationship marketing has no significant positive effect on loyalty. Shariah compliance has no significant negative effect on loyalty. Customer emotional response has a significant positive effect on loyalty. Customer emotional response is able to mediate CSR on loyalty. Customer emotional response is not able to mediate relationship marketing and shariah compliance with loyalty.